2014
DOI: 10.1038/nm.3450
|View full text |Cite
|
Sign up to set email alerts
|

Mfge8 promotes obesity by mediating the uptake of dietary fats and serum fatty acids

Abstract: Fatty acids are integral mediators of energy storage, membrane formation and cell signaling. The pathways that orchestrate uptake of fatty acids remain incompletely understood. Expression of the integrin ligand Mfge8 is increased in human obesity and in mice on a high-fat diet, but its role in obesity is unknown. We show here that Mfge8 promotes the absorption of dietary triglycerides and the cellular uptake of fatty acid and that Mfge8-deficient (Mfge8−/−) mice are protected from diet-induced obesity, steatoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 64 publications
5
118
3
Order By: Relevance
“…In vitro CRISPR knockout of ABCD1 gene in N9 microglia did not show upregulation of C1q or MFGE8 (data not shown), suggesting an indirect non‐cell‐autonomous process. Khalifeh‐Soltani et al reported MFGE8 upregulation by high‐fat treatment and demonstrated a role of MFGE8 in absorption of dietary triglycerides and the cellular uptake of fatty acids 37. In our study, increased VLCFA, in particular C26:0 LPC, triggered the expression of MFGE8, suggesting the altered metabolic milieu as one potential factor impacting MFGE8.…”
Section: Discussionsupporting
confidence: 67%
“…In vitro CRISPR knockout of ABCD1 gene in N9 microglia did not show upregulation of C1q or MFGE8 (data not shown), suggesting an indirect non‐cell‐autonomous process. Khalifeh‐Soltani et al reported MFGE8 upregulation by high‐fat treatment and demonstrated a role of MFGE8 in absorption of dietary triglycerides and the cellular uptake of fatty acids 37. In our study, increased VLCFA, in particular C26:0 LPC, triggered the expression of MFGE8, suggesting the altered metabolic milieu as one potential factor impacting MFGE8.…”
Section: Discussionsupporting
confidence: 67%
“…We have previously reported that Mfge8 promotes enterocyte FFA uptake and that serum TG levels in Mfge8 -/-mice are significantly reduced after an olive oil gavage (9). FFAs released from dietary fat in the intestinal lumen are absorbed by enterocytes and trafficked to the endoplasmic reticulum (ER) where they are esterified into TG (11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…In both mouse lines, enterocyte TG content was significantly increased after olive oil gavage despite a reduction in serum TG (Figure 1, A-C, the serum data for Mfge8 -/-mice was previously reported in ref. 9). The elevated TG content after olive oil gavage contrasts with our previously reported reduction in enterocyte TG content in Mfge8 -/-mice that have not had administration of an acute fat load (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations